Association of HLA-DQA1*06:01 and DPB1*05:01:01G alleles with susceptibility to end-stage liver disease with HBV infection in liver transplant recipients from the Zhejiang Han population, China - Lu, Genjie; He, Yanmin; Lu, Yangfang; Chen, Wei; Lu, Caide; Zhu, Faming (Frontiers in Immunology, 2025)
BackgroundIt has been reported that HLA was associated with susceptibility to various liver diseases. However, data on HLA in end-stage liver disease (ESLD) patients are limited. Therefore, this study aimed to explore the association of HLA with susceptibility to ESLD in patients undergoing liver transplantation (LT).Methods108 ESLD patients who underwent LT from July 1, 2023, to December 31, 2024, were investigated. At the same time, 453 blood donors were randomly selected as healthy controls. Their specimens were genotyped for 11 HLA loci using next-generation sequencing (NGS).ResultsThere was no significant difference in gender and ABO blood group between the two groups (P>0.05) except that ESLD patients were older (P < 0.001). The allele frequencies (AFs) of HLA-B*18:02, -C*07:02, -DRB1*12:02, -DRB1*14:54, -DQA1*01:04, -DQA1*06:01, -DPA1*02:02, -DPB1*05:01:01G and -DPB1*135:01 in ESLD were significantly higher than those of the control group (P < 0.05), while the AFs of HLA-DRB1*15:01, -DQA1*01:01, -DQA1*01:02, -DQB1*06:02, -DPA1*01:03 and -DPB1*02:01:02G were significantly lower than that of the control group (P < 0.05). However, after correction by the step-down Bonferroni method, only HLA-DQA1*06:01 and HLA-DPB1*05:01:01G were considered statistically significant (Pc < 0.05). The association between these two HLA alleles and ESLD remained significant (P < 0.05) after adjustment for age and gender by binary logistic regression analysis. Subgroup analysis further revealed that this association was primarily linked to hepatitis B virus (HBV) infection. Compared with the control group, there were statistically significant differences in 3 haplotypes with frequencies >1.00% in ESLD (P < 0.05). However, none were statistically significant after correction (Pc>0.05).ConclusionOur study suggested that HLA-DQA1*06:01 and HLA-DPB1*05:01:01G alleles may be associated with susceptibility to ESLD in liver transplant recipients, particularly in cases related to HBV infection.